2016
DOI: 10.1007/s10803-016-2930-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mimicry to Virtual Reality Avatars in Autism Spectrum Disorder

Abstract: Mimicry involves unconsciously copying the actions of others. Increasing evidence suggests that autistic people can copy the goal of an observed action but show differences in their mimicry. We investigated mimicry in autism spectrum disorder (ASD) within a two-dimensional virtual reality environment. Participants played an imitation game with a socially engaged avatar and socially disengaged avatar. Despite being told only to copy the goal of the observed action, autistic participants and matched neurotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
(52 reference statements)
4
37
0
Order By: Relevance
“…The choice of which virtual character for advice and whether they followed the advice (i.e., which door they then chose to go through) provided an implicit measure of trust (Hale et al ., 2017). Other studies recorded participants’ hand position during their interaction with a virtual character as a measurement of imitation and found that typical adults automatically imitated the virtual characters, but participants with autism spectrum conditions imitated less (Forbes et al ., 2016; Pan & Hamilton, 2015). These studies illustrate the use of VR to record implicit social behaviours which may be more revealing than traditional key‐hit measures.…”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of which virtual character for advice and whether they followed the advice (i.e., which door they then chose to go through) provided an implicit measure of trust (Hale et al ., 2017). Other studies recorded participants’ hand position during their interaction with a virtual character as a measurement of imitation and found that typical adults automatically imitated the virtual characters, but participants with autism spectrum conditions imitated less (Forbes et al ., 2016; Pan & Hamilton, 2015). These studies illustrate the use of VR to record implicit social behaviours which may be more revealing than traditional key‐hit measures.…”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
“…Second, capturing participant motion means the VR environment can be programmed to be responsive in real time, with both embodiment (see below) and realistic interactions between the participant and other objects or characters. For instance, knowing the participant's head location means that a virtual character can be programmed to orient their head and/or gaze towards participant's head (Forbes, Pan, & Hamilton, 2016;Pan & Hamilton, 2015) and to maintain an appropriate social distance by stepping back or forward (Pan, Gillies, Barker, Clark, & Slater, 2012). The ability to link the behaviour of a virtual character to the participant in real time also facilitated a series of studies on mimicry in VR, where the virtual character copies participants' head movements (Bailenson & Yee, 2007;Verberne, Ham, Ponnada, & Midden, 2013), or both head and torso movements (Hale & Hamilton, 2016).…”
Section: Displaying the Virtual Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies did use such virtual reality systems/devices [28][29][30][31][32][33][34][35][36]. However, many studies used conventional computer monitors to display virtual reality scenes with one or more avatars [37][38][39][40][41][42][43][44][45][46][47]. Hence, there is certain degree of overlap between the virtual reality based presentation mode and the conventional computer based presentation mode.…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…Due to the 360-degree virtual environment, a participant would have to turn his/her head up to 60 degrees left or right to see all avatars in the scene. Vizard is also used in [44,58] to create virtual reality scenes.…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%